Al-Qur'an and Astrophysics - Daruhadi, Gagah (Pusat Publikasi Nusantara, 2024)
The Quran, as the holy book of Muslims, has long been studied not only in religious and moral contexts, but also in scientific contexts. This study focuses on the excavation and analysis of Qur'anic verses related to astrophysical concepts, taking into account historical context and traditional interpretation. This research seeks to provide a deeper understanding of how religious texts can interact with scientific knowledge, enriching the dialogue between science and religion, and expanding the understanding of the Islamic worldview in the context of modern science. The findings include some of the relevance of Quranic verses to modern astronomy concepts, such as the expansion of the universe, the structure of galaxies, and the orbit of celestial bodies. In addition, this study emphasizes the importance of considering historical, cultural, and linguistic contexts in the interpretation of religious texts.